2010
DOI: 10.1111/j.1365-2745.2009.01623.x
|View full text |Cite
|
Sign up to set email alerts
|

Canopy seed storage is associated with sexual dimorphism in the woody dioecious genus Leucadendron

Abstract: Summary1. Species of the dioecious South African plant genus Leucadendron vary strikingly in their degree of sexual dimorphism, with males of dimorphic species typically possessing more and thinner branches and smaller leaves than the corresponding females. 2. Many Leucadendron species are serotinous, with females of serotinous species maintaining seeds in transpiring cones for a number of years. Since cones must be kept alive, serotinous females presumably incur higher costs in terms of water loss than non-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
86
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(92 citation statements)
references
References 49 publications
1
86
5
Order By: Relevance
“…Samples of female, male and non-reproductive plants exhibit male-biased sex ratios in four younger populations, but close to even sex ratios in older populations in which all individuals were reproductively mature (figure 2). This pattern is most probably explained by the longer time required for females to reach reproductive maturity because of costs associated with serotinous cone production (see Harris & Pannell 2010), and assumes that non-flowering individuals in the younger populations examined are largely female. Populations of most dioecious species are composed of mixed age cohorts and it is therefore more difficult to assess the influence of age on sex ratio dynamics.…”
Section: Sex Ratio Variation In Dioecious Plant Populationsmentioning
confidence: 96%
“…Samples of female, male and non-reproductive plants exhibit male-biased sex ratios in four younger populations, but close to even sex ratios in older populations in which all individuals were reproductively mature (figure 2). This pattern is most probably explained by the longer time required for females to reach reproductive maturity because of costs associated with serotinous cone production (see Harris & Pannell 2010), and assumes that non-flowering individuals in the younger populations examined are largely female. Populations of most dioecious species are composed of mixed age cohorts and it is therefore more difficult to assess the influence of age on sex ratio dynamics.…”
Section: Sex Ratio Variation In Dioecious Plant Populationsmentioning
confidence: 96%
“…A study analyzing the sex ratios of 126 dioecious species has showed nearly continuous variation from strong male to strong female bias, and exhibit male‐biased sex ratios in some younger populations, but close to even sex ratios in older populations in which all individuals were reproductively primary (Barrett, Yakimowski, Field, & Pickup, 2010). In an ultimate manner, the changing sex ratio was attributed to the longer time required for females to reach reproductive maturity because of costs associated with serotinous cone production (Harris & Pannell, 2010), in which significant resource is also invested.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, this result accords with the predictions that there are clear tradeoffs between vegetative and reproductive matters. Harris and Pannell (2010) reported that females of highly serotinous species were less branched than males in dioecious Leucadendron. Another study showed more branches and smaller leaves in males than in females (Midgley 2010).…”
Section: Gender-related Allometric Relationshipsmentioning
confidence: 99%